Impregnation of palm shell activated carbon with polyethyleneimine and its effects on Cd2+ adsorption - Yin, C.Y.; Aroua, M.K.; Daud, W.M.A.W. (Elsevier, 2007)
Palm shell activated carbon (AC) was impregnated with low (LMW) and high molecular weight (HMW) polyethyleneimine (PEI) via batch adsorption. The maximum amount of LMW PEI adsorbed on AC was determined to be approximately 425 mg/g carbon while the maximum adsorbed HMW PEI was 2.8 mg/g carbon. The LMW PEI adsorption data fitted the Langmuir isotherm better than the Freundlich isotherm. The PEI impregnated AC were characterized via nitrogen adsorption, scanning electron microscopy, elemental analysis, thermogravimetric, Fourier transform infra red and pH drift analyses. Only LMW PEI could be successfully impregnated as monolayers on the surface of the micropores. This impregnation leads to drastic reduction of surface area and pore volume whereas impregnation of HMW PEI does not significantly affect the physical characteristics of the AC. LMW PEI impregnation appears to enhance Cd2+ adsorption capacity of the AC while HMW PEI impregnation is found to have an opposite effect. This result shows that LMW PEI impregnation technique may have the potential to improve the batch adsorption capacity of AC for other transition metal ion adsorption as well.